ANXIETY IN JOHN GREEN’S NOVEL THE FAULT IN OUR STAR - Anastasya Al Zamzami; Sri Wulan (JOURNAL OF LANGUAGE, 2023)
This study aims to reveal the type of anxiety experienced by the protagonist and her defense mechanisms against the anxiety in John Green’s novel The Fault in Our Star. The causes of anxiety can be seen for the first time when Hazel is diagnosed with thyroid cancer. That situation results in a big impact on people around her, especially her parents' boyfriends. They get worried that she will hurt the people around her. This study uses the psychoanalytic theory of Sigmund Freud to explain the protagonist's type of anxiety and her defense mechanisms to get rid of the anxiety. In completing the analysis, this study applies the qualitative research method because the data collected in this study are in the form of words as quotations taken from the source. The results of this study indicate that the first protagonist's anxiety is caused by feeling guilty, overthinking, and worrying about keeping an eye out for the future. Therefore, two types of anxiety can be found in the novel. They are moral and realistic anxieties. Then, the protagonist commits two defense mechanisms to avoid her anxiety. They are rationalization and reaction formation. Finally, this data proves that the protagonist in the novel suffers from anxiety, and she tries hard to cure the disease.